2020
DOI: 10.3389/fcvm.2020.00059
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Disorders of Pregnancy and Future Cardiovascular Health

Abstract: Hypertensive disorders of pregnancy (HDP) occur in almost 10% of gestations. These women are known to have higher cardiovascular morbidity and mortality later in life in comparison with parous controls who had normotensive pregnancies. Several studies have demonstrated that women with preeclampsia present in a state of segmental impaired myocardial function, biventricular chamber dysfunction, adverse biventricular remodeling, and hypertrophy, a compromised hemodynamic state and indirect echocardiographic signs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 106 publications
(68 reference statements)
3
70
0
9
Order By: Relevance
“…Non-infectious causes worthy of consideration in this case were pre-eclampsia, eclampsia and acute fatty liver of pregnancy. Her normal antenatal blood pressure records, absence of proteinuria, and acute presentation made hypertensive disorders implausible [18]. Acute fatty liver of pregnancy presents with non-specific signs and symptoms, such as nausea, vomiting, fatigue and anorexia, leading eventually to liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…Non-infectious causes worthy of consideration in this case were pre-eclampsia, eclampsia and acute fatty liver of pregnancy. Her normal antenatal blood pressure records, absence of proteinuria, and acute presentation made hypertensive disorders implausible [18]. Acute fatty liver of pregnancy presents with non-specific signs and symptoms, such as nausea, vomiting, fatigue and anorexia, leading eventually to liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…To this point, it is hypothesized to cause some of these APOs, such as preeclampsia, preeclampsia with severe features, eclampsia, or preeclampsia superimposed on chronic hypertension. 25 The American Heart Association has already recognized these conditions as independent risk factors for CVD and introduced these complications of pregnancy in the algorithms for the evaluation of future cardiovascular risk scores. 26 These are classified as hypertensive disorders of pregnancy, in addition to gestational hypertension, defined as new-onset hypertension after 20 weeks of gestation, or chronic hypertension.…”
Section: Strategies To Improve Awareness At a Digital Industry And mentioning
confidence: 99%
“…It has also been shown that women with a history of PE have an up to five-to 12-fold increased risk of developing end-stage renal disease later in life [11,13]. The association between PE and future CVD is no surprise given the fact that several studies have revealed that women with PE are in a state of cardiac dysfunction [5,14]. PE has been shown to be associated with cardiovascular changes such as a decrease in cardiac output, increased systemic vascular resistance and left ventricular diastolic dysfunction [5,6,14,15].…”
Section: Introductionmentioning
confidence: 99%